A Review on “Image Steganography with LSB & DWT Techniques” - Neha,; Mohit, (International Journal of Computer Sciences and Engineering, 2025)
In all the fields of steganography such as image, text, audio, video there are many techniques used totransfer the secret messages without known to other person. Using the Steganography technique to hide the data or message in an image,LSB and DWT are two easy techniques which are usefull and implemented easily to improve robustness and performance of algorithms. LSB method used to transfer the large data and replace some information in pixel with information from the data in image. Overall use of LSB doesn’t affect the representation of image. In this technique, LSB method will be used to transfer the large data and replace some information in pixel with information from the data in an image.DWT method is used to embed converted data into cover medium to conceal its presence. For the security, we will use the technique DWT which is used with the low frequency (used for narrow bandwidths) and high frequencies (for wider bandwidths) and for the flexibility.